English methods of birth control - Sanger, Margaret, 1879-1966
1915 1915 1910s 18 pages 5 ARE PREVENTIVE METHODS INJURIOUS TO HEALTH? One of the questions quite commonly asked by women and men who are fearful of using preventives is: "Will preventive methods injure the health of either the man or the woman?" A prominent authority, Wille (as quoted by Kisch), maintains "that the continued fear of pregnancy will in most cases do more injury to the feminine system than all the preventive measures in the world." It is further claimed by some physicans [physicians] that to a nervously weak woman a preventive method is almost necessary, and even helpful in regaining her health ; but that much depends upon the kind of method employed is not doubted. One of the most directly injurious methods to the woman is the use of strong solutions of antiseptics for the douche. If these are above the proper strength, they are liable to injure the delicate membraneous lining of the parts. The same solutions in weaker proportions will act as a cleanser, and are seldom injurious. But as each person is susceptible in a greater or less degree to all drugs, I advise the use of salt solution as a douche, as not only the least injurious and the cheapest, but as most beneficial. Another question which has arisen in late years is the possibility that preventive methods have caused cancer. There is very little foundation for this assertion. The constant use of the pessary, worn from month to month, or the "uterus button," worn by women in the Western States, or any mechanical means worn constantly, might give rise to an irritation which could lead to the growth of cancer. But the temporary use of either of these would without doubt be quite harmless. By temporary use, I mean the use of either only when needed, followed by their removal. In employing any preventive measures there is almost no danger to the man at all, even the habit of "coitus interruptus," or withdrawal, which is the most common method practised everywhere, is not considered as dangerous to the man's health, 15X/2/566/51